2012
DOI: 10.1038/nn.3155
|View full text |Cite
|
Sign up to set email alerts
|

P2X4R+ microglia drive neuropathic pain

Abstract: Neuropathic pain, the most debilitating of all clinical pain syndromes, may be a consequence of trauma, infection or pathology from diseases that affect peripheral nerves. Here we provide a framework for understanding the spinal mechanisms of neuropathic pain as distinct from those of acute pain or inflammatory pain. Recent work suggests that a specific microglia response phenotype characterized by de novo expression of the purinergic receptor P2X4 is critical for the pathogenesis of pain hypersensitivity caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
293
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(299 citation statements)
references
References 45 publications
(52 reference statements)
5
293
1
Order By: Relevance
“…Data has been presented to indicate that antagonism of spinal P2X3/P2X2/3 receptors regulates an indirect activation of the opioid system to alleviate inflammatory hyperalgesia [105]. P2X4 receptors probably also participate because of their involvement in neuropathic pain [106,107], which is relevant for inflammation. Mice lacking P2X4 receptors show impaired inflammasome activation [40] and do not develop pain hypersensitivity in response to inflammatory agents, and this is paralleled by a complete absence of PGE 2 in inflammatory exudates [30].…”
Section: Inflammatory Painmentioning
confidence: 99%
“…Data has been presented to indicate that antagonism of spinal P2X3/P2X2/3 receptors regulates an indirect activation of the opioid system to alleviate inflammatory hyperalgesia [105]. P2X4 receptors probably also participate because of their involvement in neuropathic pain [106,107], which is relevant for inflammation. Mice lacking P2X4 receptors show impaired inflammasome activation [40] and do not develop pain hypersensitivity in response to inflammatory agents, and this is paralleled by a complete absence of PGE 2 in inflammatory exudates [30].…”
Section: Inflammatory Painmentioning
confidence: 99%
“…Spinal cord microglia quickly react to injury (including peripheral nerve damage), by first acquiring a phagocytic phenotype and then releasing large amounts of inflammatory mediators [63]. This pro-inflammatory extracellular milieu can dramatically influence synaptic activity and neuronal firing of second-order neurons in the spinal cord dorsal horn, and ultimately contribute to the generation and maintenance of chronic neuropathic pain [63].…”
Section: Spinal Cord Microglia and Astrocytesmentioning
confidence: 99%
“…This pro-inflammatory extracellular milieu can dramatically influence synaptic activity and neuronal firing of second-order neurons in the spinal cord dorsal horn, and ultimately contribute to the generation and maintenance of chronic neuropathic pain [63].…”
Section: Spinal Cord Microglia and Astrocytesmentioning
confidence: 99%
“…It has also been reported that expression of the ligand-gated ion channel pregnane 2 recepter (P2X) receptor is increased in activated microglia. 8,[10][11][12] This induces the release of brain-derived neurotrophic factor (BDNF) from microglia, which binds to the tyrosine kinase receptor B (TrkB) receptor on secondary sensory nerves, downregulating the expression of K-Cl cotransporter 2 (KCC2). 13,14) The reduced expression of KCC2 disinhibits GABAergic neurons, which suppress the sensation of pain under normal conditions, resulting in pain enhancement.…”
mentioning
confidence: 99%